Common seasonal respiratory viral infections in children before and during the coronavirus disease 2019 (COVID-19) pandemic. (5th October 2022) - Song, Xiaoyan; Delaney, Meghan; Shah, Rahul K.; Campos, Joseph M.; Wessel, David L.; DeBiasi, Roberta L.
Abstract: Objectives: To describe the incidence of seasonal respiratory viral infections (s-RVIs) before and during the coronavirus disease 2019 (COVID-19) pandemic and to compare virus-specific patient outcomes in pediatric patients. Design: A retrospective cross-sectional study including patient admissions to the Children's National Hospital between October 1, 2015, and December 31, 2020. Results: Among 12, 451 patient admissions between March 15 and December 31, 2020 (cohort 1), 8, 162 (66%) were tested for severe acute respiratory coronavirus virus 2 (SARS-CoV-2), and 249 (2.0%) were positive. Among 10, 986 patient admissions between April 1 and December 31, 2020 (cohort 2), 844 (8%) were tested for s-RV upon admission and 160 were positive. Thus, 1.5% of patient admissions were associated with laboratory-confirmed s-RVIs. Among the 49, 901 patient admissions during a viral season between October 1, 2015, and March 31, 2020 (cohort 3), 7, 539 (15%) were tested for s-RV upon admission and 4, 531 were positive; thus, 9.0% of patient admissions were associated with laboratory-confirmed s-RVIs. hHRV/rENT was the most detected virus, but the detection rate decreased substantially (31% vs 18%; P < .001) during the COVID-19 pandemic. No patients had RSV, influenza, hMPV, hPIV, or hCoV detected upon admission after April 21, 2020. The 3 patient cohorts had no statistically significant difference in the percentage of ICU admissions (10.8% vs 15.0% vs 14.2%; P > .05) or death at discharge (0.8% vs 0.6% vs 0.5%; P > .05). Conclusions: Compared to COVID-19, s-RVI cases were associated with a higher proportion of inpatient admissions but were similar in ICU admission and death rates in hospitalized pediatric patients. Public health interventions for preventing COVID-19 were highly effective in preventing pediatrics s-RVIs.